The Feasibility and Positive Effects of Wuqinxi Exercise on the Cognitive and Motor Functions of Patients with Parkinson's Disease: A Pilot Study. (30th March 2021) - Shen, Mengyue; Pi, Yan-Ling; Li, Zhenlan; Song, Tao; Jie, Kuncheng; Wang, Tian; Guo, Wei; Zhuang, Jie; Wang, Zhen
Abstract : Introduction . Parkinson's disease (PD) is a chronic degenerative disease of the central nervous system common in middle-aged and elderly people, which has a serious impact on patients' cognitive and motor functions. Exercise can improve the nonmotor symptoms of PD patients, but the optimal type of exercise for the cognitive function of patients is unclear. Therefore, the purpose of this study is the impact of 12 weeks of Wuqinxi exercise on the cognitive and motor function in PD patients. Methods . Thirty PD patients participated in the study and were randomly assigned to two groups: Wuqinxi group ( n = 15) or stretching group ( n = 15). All the participants performed a 12-week exercise program twice a week, 90 min/session. The assessments were conducted before and after exercise intervention, included cognitive function (frontal assessment battery (FAB); Stroop test I and II), motor functions (Unified Parkinson's Disease Rating Scale Part III (UPDRS-III); timed up and go (TUG)). Results . We found the FAB and Stroop I scores were significantly higher in the Wuqinxi group than in the stretching group. Participants in the Wuqinxi group significantly improved their UPDRS-III (17.73 ± 9.88) and TUG (10.50 ± 1.79) score after 12 weeks of training intervention. Conclusion . The results show that the use of Wuqinxi for rehabilitation therapy for cognition is feasible, widely accepted, and effective in patients with Parkinson's disease. This study provides preliminary evidence for further large-scale and controlled studies.